Words Echoing Through Time: The Melody of Learning with A Voice Translator App - Basopi, Pegiawan (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
This study explores the effectiveness of voice translator apps in enhancing students' interest in learning vocabulary. Conducted on students of SMAN 1 Terara, an Indonesian high school, who are learning English as a foreign language, the study aims to examine the impact of voice translators on their motivation and interest in learning vocabulary, as well as their vocabulary acquisition. Using Classroom Action Research as the research design, 30 students from the first grade of SMAN 1 Terara were selected as participants. The results indicate that using a voice translator application can positively impact students' vocabulary acquisition and interest in learning. The study highlights the importance of understanding the effectiveness of voice translator applications to develop more effective language learning and teaching strategies. Nevertheless, the study has some limitations, and further research is necessary to understand the long-term effects of using the application.